1978
DOI: 10.1039/c39780000193
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical course of dehydration catalysed by the yeast fatty acid synthetase

Abstract: Dehydration of the (3R)-hydroxyalkyl S-thioester (1) by yeast fatty acid synthetase to give the trans-2-enoyl derivative (2) occurs by means of a synelimination of the elements of water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…This is in contrast to the demonstrated specificity of EryDH4, TylDH2, and NanDH2, all of which utilize only (2 R ,3 R )-2-methyl-3-hydroxyacyl-ACP substrates, as well as the specificity of the DH domain of yeast FAS for 3 R -hydroxyacyl-ACP substrates. 55 Intriguingly, the intrinsic preference of RifDH10 for the (2 S ,3 S )-2-methyl-3-hydroxyacyl thioesters is only evident when the substrate is tethered to its native acyl carrier protein, RifACP10. By contrast, RifDH10-catalyzed dehydration of the corresponding non-cognate EryACP6, as well as the NAC and pantetheine thioester analogues is specific for the corresponding (2 R ,3 R )-2-methyl-3-hydroxyacyl diastereomers, while in no case do either the (2 R ,3 S )- or (2 S ,3 R )-2-methyl-3-hydroxyacyl derivatives undergo dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the demonstrated specificity of EryDH4, TylDH2, and NanDH2, all of which utilize only (2 R ,3 R )-2-methyl-3-hydroxyacyl-ACP substrates, as well as the specificity of the DH domain of yeast FAS for 3 R -hydroxyacyl-ACP substrates. 55 Intriguingly, the intrinsic preference of RifDH10 for the (2 S ,3 S )-2-methyl-3-hydroxyacyl thioesters is only evident when the substrate is tethered to its native acyl carrier protein, RifACP10. By contrast, RifDH10-catalyzed dehydration of the corresponding non-cognate EryACP6, as well as the NAC and pantetheine thioester analogues is specific for the corresponding (2 R ,3 R )-2-methyl-3-hydroxyacyl diastereomers, while in no case do either the (2 R ,3 S )- or (2 S ,3 R )-2-methyl-3-hydroxyacyl derivatives undergo dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…18 The structure of the E. coli dehydratase (FabA) displays a characteristic hotdog fold that has been observed in all other DH structures from both FAS and PKS systems. 7a,19,20 The active site of each DH harbors a universally conserved pair of His and Asp residues.…”
Section: Discussionmentioning
confidence: 96%
“…Schwab, in a critical review of research on FabA and the closely related dehydratase-isomerase FabZ, has discussed a one-base, two-step mechanistic model in which the active site imidazole residue first catalyzes the stereospecific removal of 2-H si of the 3-hydroxyacyl-ACP substrate following which the transiently-generated imidazolium species donates its proton to the 3-hydroxyl group to promote C–O bond cleavage. 18a,21,22 Although the distinct enoyl-CoA hydratase of fatty acid oxidation differs significantly from DH enzymes in both protein fold and the presence of two essential active site Glu residues in place of the His-Asp dyad of DH domains, it catalyzes an analogous net syn hydration of ( E )-2-enoyl-CoA thioesters to yield the corresponding (3 S )-3-hydroxyacyl-CoA products. 17a Both protons and the oxygen of the nucleophilic water are incorporated into the product, consistent with a single-base mechanism for enoyl-CoA hydratase in which one Glu residue acts sequentially, first as base and then as active site acid, while the second Glu side chain positions the active site water by an essential H-bond.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from this study, no other reports probe the substrate preference or catalytic mechanism of DH domains within PKS systems; therefore, much of what is known has been elucidated from studies of fatty acid biosynthesis (28). Previous studies on the dehydration step that is catalyzed by the yeast fatty acid synthase confirmed the syn elimination of water from a D-(3 R)-hydroxyacylthioester substrate (29). This result is consistent with the stereospecificity of the PKS DH domain and may suggest that trans unsaturated bonds, typically found in polyketides, are likewise formed via syn water elimination.…”
Section: Trans Double Bondsmentioning
confidence: 97%